The Effectiveness of the Monitoring Card on the Motivation of Pregnant Women with Chronic Energy Deficiency (CED) in Monitoring Pregnancy Development in West Lombok Regency - Syajaratuddur Faiqah; Ati Sulianty; Mutiara Rachmawati Suseno; Baiq Yuni Fitri Hamidiyanti (poltekkes kemenkes mataram, 2022)
Chronic Energy Deficiency (CED) is a condition in which a person's nutritional status is poor due to a lack of consumption of food sources of energy that contain macronutrients. The results of Basic Health Research 2013, showed that CED in pregnant women was 24.1%, decreased in 2018 by 17.3%, in West Lombok Regency in 2018, the prevalence of CED was 13.36%. , and increased in 2019 to 14.0%. This study aims to determine the effectiveness of the monitoring card on the motivation of pregnant women with CED in monitoring pregnancy development in the West Lombok Regency. This study is a quasi-experimental study with a total sample of 52 people, which were divided into an intervention group and a control group. The data collected were in the form of pregnancy development monitoring data, pre-test and post-test data on the motivation of pregnant women. The results of the Independent T-test statistic in the pre-test showed that there was no difference in the mean motivation of pregnant women with CED (p-value: 0.828; p > 0.05). While the post-test results obtained a P-value: 0.001 it can be concluded that there is a difference in the average motivation score between CED pregnant women who are given a monitoring card and CED pregnant women with the MCH Handbook. Based on the results of the study, it can be concluded that the monitoring card is effective in increasing the motivation of pregnant women with CED in monitoring the progress of the pregnancy.